2019
DOI: 10.1111/jtxs.12487
|View full text |Cite
|
Sign up to set email alerts
|

How sensory sensitivity to graininess could be measured?

Abstract: Considering the lack of the literature and the need for developing a valid method to measure the texture sensitivity, in this study, we investigated the individual sensitivity to discriminate among different levels of graininess. With this purpose, five samples of cocoa‐based creams were prepared, by changing the refining time. Samples were first characterized in terms of particles size distribution, by means of laser diffraction. Then, 59 subjects evaluated the cream sample graininess intensity, by using gLM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
12
2
Order By: Relevance
“…As reported in the literature, the human graininess detection threshold is higher in high viscous suspensions and gels than the same in low viscous and aqueous suspensions (Imai, Hatae, & Shimada, 1993). Therefore, the study conducted by Puleo, Miele, Cavella, Masi, and Di Monaco (2019) demonstrated that differences in terms of graininess ranging from 25 to 30 µm were not perceived as significant, also considering high sensitive subjects to the graininess. However, assessors were able to discriminate the samples for the number of granules.…”
Section: Resultsmentioning
confidence: 97%
“…As reported in the literature, the human graininess detection threshold is higher in high viscous suspensions and gels than the same in low viscous and aqueous suspensions (Imai, Hatae, & Shimada, 1993). Therefore, the study conducted by Puleo, Miele, Cavella, Masi, and Di Monaco (2019) demonstrated that differences in terms of graininess ranging from 25 to 30 µm were not perceived as significant, also considering high sensitive subjects to the graininess. However, assessors were able to discriminate the samples for the number of granules.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, it was assumed that sensory scores should follow the same trend exhibited by the instrumentally measured stress overshoot, with the increase in the solid concentration, that is, an upward linear relationship. Thus, the flowability scores of each subject were fitted with a linear equation, according to Puleo and colleagues [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], estimating both the slope and the R 2 coefficient and using them as clustering parameters according to the quartile distribution ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Repeated-measures ANOVA and a multiple comparison test (Duncan’s test) were used to evaluate whether differences among the samples (used as a repeated factor) were statistically significant ( p ≤ 0.05) in terms of perceived flowability. At the same time, subjects were split into three groups, lowly sensitive (LS), moderately sensitive (MS) and highly sensitive (HS), according to the approach proposed by Puleo et al [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], considering that HS subjects have a discrimination ability comparable to the instrument.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations